Situated Causality: What Ethnography Can Contribute to Causal Inquiry in Social Work. (25th March 2021) - Mathias, John; Doering-White, John; Smith, Yvonne; Hardesty, Melissa
Abstract: This article considers how ethnography can contribute to developing causal theories relevant to social work practice. Social work researchers typically reserve causal inferences for studies that rely on certain quantitative study designs, and ethnography tends to be seen as insufficient for making causal claims. Integrating data from three ethnographies of social work practice, this article posits that ethnography is particularly well equipped to (a) identify causal processes that do not fit existing academic theories, (b) document causal theories implicit in social action, and (c) examine how competing causal theories are contested. Such contributions can enrich causal inquiry that has traditionally prioritized prediction (what is the likelihood of this happening?) over explanation (how does this work?). This is consistent with recent calls for attention to causal mechanisms in implementation science and other fields. Ethnography can expand the causal vocabulary of social work research, bringing depth and nuance to causal theories while also making these theories more amenable to uptake by practitioners.